Analysis of The Use of Indonesian Language in Public Spaces of Transportation Services PT IRA Trans Medan - Nababan, Deminar; Ahmad Laut Hasibuan (PT Inovasi Pratama Internasional, 2025)
The objectives of this study are to analyze the use of good and correct Indonesian in PT Ira Trans Medan Transportation Services in 2024 and to analyze the main factors that cause errors in the use of Indonesian by drivers, conductors, and passengers at PT Ira Trans Medan in 2024. The research method used in this study is qualitative. This study highlights the importance of policies that support the use of Indonesians according to rules in public spaces. Practical implications for PT Ira Trans: Improve training and improve communication media and for the government: Tighten language control in public spaces. The conclusions are that the use of Indonesian in PT Ira Trans Medan is often not in accordance with the rules; factors causing errors include lack of knowledge and indifference to language rules, and company policy has not paid special attention to the use of Indonesian in public spaces